ANTIHIPERURESEMIA FLAVONOID DARI EKSTRAK ETANOL PELEPAH DAUN NIPAH (Nypa fruticans.Wurmb) - Raharjo, Danang; Dwi S, Anita; Ardiyantoro, Bagas (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Hyperuresimia or gout in advanced stages causes joint damage (gout), kidney stones and kidney damage. Flavonoids as antioxidants can inhibit the activity of the enzyme xanthine oxidase which causes uric acid not to form. Nypa fruticans or known as nipah is traditionally used in the treatment of asthma, leprosy, tuberculosis, sore throat, liver disease, snake bites, as a pain reliever, as a sedative and carminative. The content of flavonoid compounds in nipah plants includes chlorogenic acid, protocatechuic acid, kaempferol, gallic acid, hydroxybenzoic acid, rutin, quercetin, cinnamic acid, and anthocyanins. The purpose of this study was to isolate flavonoid compounds that have potential as antihyperuresemia from nipah fronds. The research process began with the extraction of nipah leaves using 96% ethanol by maceration, fractionation using liquid-liquid partition method, isolation using centrifugal chromatography (chromatotron) method and structure elucidation using 1HNMR, 13CNMR, FTIR and GC-MS. Antihyperuresemia testing was carried out in-vitro by inhibiting xanthine oxidase enzyme activity. From the results of the study, two flavonoid compounds were successfully isolated including (-) epicatechin, and chamferol. The results of measuring the inhibitory activity of xanthine oxidase enzyme obtained IC50 values of (-) epicatechin and chamferol of 3.543 ppm and 10.383 ppm, respectively.